(untitled) (Med Phoenix, 2023)
Introduction: Intensivist and Nephrologist generally place the dialysis catheter to obtain vascular access for immediate and short-term haemodialysis. We hereby present a case of a 54 years male with a past history of diabetes mellitus, hypertension, and chronic kidney disease stage four who was planned for immediate haemodialysis for severe hyperkalaemia and metabolic acidosis. A haemodialysis catheter was inserted under ultrasound guidance through the right internal jugular vein, but during the procedure, the guidewire was pushed into vein. The chest X-ray showed the looping of the tip of a guidewire. It was successfully surgically extracted, haemodialysis was done through the right femoral vein successfully, and the patient was discharged. From this, we want to emphasize that accidental migration is a fatal, avoidable, preventable complication. Simple measures like holding the guidewire until removal from vessels, vigilant supervision of the trainees, avoidance of vigorous force during insertion of guidewire may prevent this complication.